Geoinformation system for monitoring forest fires and data encryption for low-orbit vehicles - Khuralay Moldamurat; Makhabbat Bakyt; Dastan Yergaliyev; Dinara Kalmanova; Anuar Galymzhan; Abylaikhan Sapabekov (Computer Science and Information Technologies, 2025)
This article discusses two important aspects of unmanned aerial vehicles (UAVs): forest fire monitoring and data security for low-orbit vehicles. The first part of the article is devoted to the development of a geographic information system (GIS) for monitoring and forecasting the spread of forest fires. The system uses intelligent processing of aerospace data obtained from UAVs to timely detect fires, determine their characteristics and forecast the dynamics of development. The second part of the article focuses on the problem of high-speed encryption of data transmitted from low-orbit aircraft. An effective encryption algorithm is proposed that ensures high data processing speed and reliable protection of information from unauthorized access. The article presents the results of modeling and analysis of the effectiveness of the proposed solutions.